pengaruh Capital, Assets, Management, Earnings, Liquidity Dan Sensitivity Of Market (CAMELS) Terhadap Return Saham Pada Perusahaan Perbankan Go Public - Christie, Jessica (JURNAL RISET BISNIS DAN MANAJEMEN, 1996)
The more competitive the banking sector cause to the increased management banking financial management which professionals in order to increase the value added in order to develop bank-backed fund inflows, stimulating the banking industry in Indonesia to go public. Banks go public have the obligation to publish financial statements. Based on the financial report will be calculated a number of financial ratios commonly used as the basis of the rating of the bank. Based on the results of regression analysis, simultaneously, a CAMELS method is not influence significantly on Stock Return as simultaneous, but partially concerning LDR variable that significantly influence the Stock Return meanwhile other variables namely CAR, NPL, NPM, ROA, IER not significant. Keywords: CAR, NPL, NPM, ROA, LDR, IER, Stock Return